Keefektifan Model Pembelajaran Think Talk Write (TTW) dan Cooperative Integrated Reading and Composition (CIRC) dalam Keterampilan Menulis - Nina Prince Simorangkir; Ramly Ramly; Ambo Dalle; Johar Amir (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Writing news text is a part of language skills that are considered difficult, influenced by internal and external factors. Therefore, a creative and innovative learning model is needed that can motivate and encourage children to write, think critically, and investigate issues when creating news articles. The purpose of this study is to evaluate the efficacy of the Cooperative Integrated Reading and Composition (CIRC) and Think Talk Write (TTW) methods in developing news text writing skills in grade VII students. An experiment is the technique employed through a nonequivalent control group design, involving two groups: experimental and control. Information was gathered from news text writing tests in the form of descriptive questions (pre-test and post-test) then analyzed descriptively quantitatively. The results showed that in the control class (TTW), the mean score of students reached 75.33 with a standard deviation of 7.89; as many as 83.33% of students achieved the passing grade. In the experimental class (CIRC), the average score reached 79.00 with a standard deviation of 6.49, and 96.64% of students achieved the passing grade. Thus, the TTW and CIRC models are equally effective in improving news text writing skills, but CIRC is more optimal. Further it is advised to do research to increase the sample size and explore the effect of duration and frequency of application of this model on other language skills or different levels of education.